Intelligent Fault Detection and Self-Healing Architectures in Distributed Software Systems for Mission-Critical Applications (International Journal of Scientific Research and Management (IJSRM), 2024)
Self-healing and intelligent fault detection systems are very vital frameworks if we are to raise the dependability and resilience of distributed software systems in mission-critical applications. By use of contemporary technologies including predictive analytics, machine learning, and adaptive algorithms, these systems independently repair errors, actively evaluate system health, and find anomalies: Among the techniques these systems apply to keep low operational costs, continuous service delivery, and little downtime are redundancy, failover systems, and real-time diagnostics. Systems with self-healing capability offer scalability and fault tolerance in both dynamic and demanding environments as well as in optimal performance with various workloads. Using reference to its main features, advantages, and techniques, this book discusses intelligent defect management. The focus is on how these satisfy the dependability standards in domains such aviation, finance, and healthcare. This highlights the possibility to reorganise these systems to enhance operational resilience and efficiency, hence strengthening the dependability and autonomy of dispersed systems.